Bovine macrophages responses to the infection with virulent and attenuated Leptospira interrogans serovar Pomona - Nagel, Ariel Gaston; Vazquez, Cristina Lourdes; Etulain, Julia; Blanco, Federico Carlos; Gravisaco, María José; Gomez, Ricardo Martín; Caimi, Karina Cynthia (Elsevier, 2019)
Leptospirosis is a zoonosis, caused by pathogenic spirochetes of the genus Leptospira. Although cattle are usually the maintenance hosts of serovar Hardjo, Pomona is the most frequent serovar circulating in Argentina. The understanding of bovine innate immune response and the virulence of this serovar is important for future control measures. This work compares infection of bovine macrophages with the virulent L. interrogans sv Pomona strain AKRFB (P1) and its attenuated counterpart (P19). First, we confirmed attenuation in the hamster model. Mortality and lung hemorrhages occurred after P1 inoculation, while the survival rate was 100% in P19-infected animals. Cells infected with both strains showed statistically upregulated gene expression of pro-inflammatory cytokines, IL-1β, IL-6 and TNFα. The level of expression of anti-inflammatory cytokine IL-10 was statistically different between strains. Increased expression of IL-10 was observed only in P1-infected cells. For the first time, we describe macrophages extracellular traps induced by infection of bovine macrophages (bMETs) with both, the virulent and attenuated Leptospira interrogans Pomona strains. P1 was found higher internalized when the phagocytosis was inhibited, suggesting a cell entrance of this strain also by an independent-phagocytosis pathway. Furthermore, P1 was higher colocalized with acidic and late endosomal compartments compared with P19. This data emphasizes the importance to deepen in Leptospira bovine macrophages particular invasion mechanisms and, furthermore, underline the value of studying the main hosts.